(untitled) (Ustozlar uchun, 2026)
This study examines the verbalization of the concept “woman” in English quotations, focusing on both image-bearing and evaluative components. The analysis explores how metaphorical expressions and culturally embedded meanings construct the conceptual image of a woman in modern discourse. Using conceptual, contextual, and descriptive analytical methods, the research identifies dominant semantic features associated with women, including strength, resilience, beauty, empowerment, and transformation. The findings demonstrate that the contemporary representation of women is largely positive, emphasizing empowerment, individuality, emotional strength, and social agency. The study concludes that language reflects ongoing socio-cultural shifts regarding gender roles and identity, revealing a movement toward positive and empowering portrayals of women.